Modeling Trophic Cascades to Identify Key Mammalian Species for Ecosystem Stability - Idung Risdiyanto; Yanto Santosa; Nyoto Santoso; Arzyana Sunkar (Ecologies)
The role of keystone species in maintaining ecosystem stability is a crucial aspect of ecology. Identifying key mammalian species within an ecosystem requires a systematic approach, utilizing criteria and indicators derived from species characteristic variables. This study presents a framework to identify key mammalian species based on various ecological, structural, and functional factors. By developing a mechanistic model of energy flow in food webs and trophic levels, the model aims to pinpoint each species’ role in the stability and sustainability of biomass flow within the ecosystem. Known as KVT version 1.0, the model explains the role of each characteristic variable of mammalian species, predicts population growth, elucidates species interactions at trophic levels, and assesses species-specific dietary compositions, including food requirements, reproduction, and activity. Factor analysis of model outputs has produced equations to determine the value of keystone species (Kv), indicating the role of mammalian species in the stability and sustainability of biomass flow in the ecosystem. Keystone species, as identified by this model, are primarily small mammals of the families Muridae, Sciuridae, Tupaiidae, Ptilocercidae, Hystricidae, Viverridae, and Herpestidae, demonstrating omnivorous and herbivorous trophic levels. This model can serve as a valuable framework for conservation management of biodiversity in an ecosystem, with potential for expansion to include characteristics of non-mammalian species in future research.